Cutaneous and Neurological Manifestations as Predictors of Progressive Fibrosing Phenotype in CTD-ILD - Kashif Sardar, Ubaid Ullah Ansari, Shoaib Saleem Khan, Nighat Fatima, Zahid Habib Qureshi, Bakhtawar Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Connective tissue disease-associated interstitial lung disease (CTD-ILD) is an important cause of respiratory morbidity in patients with systemic autoimmune disorders. Some patients are characterized by a progressive fibrosing phenotype and experience an increase in fibrotic change on high-resolution computed tomography, along with progressive symptomology and pulmonary function. This study assessed whether there were any skin and/or nerve features that could predict the progressive fibrosing phenotype in CTD-ILD. Methods: This prospective observational study was conducted at Multan Medical and Dental College, Multan, in collaboration with Nishtar Medical University, Multan, from January 2022 to January 2023. A total of 100 patients with definite CTD-ILD were included. Demographic characteristics, connective tissue disease subtype, cutaneous findings, neurologic findings, pulmonary function parameters, laboratory markers, and HRCT findings were documented. The progressive fibrosing phenotype was characterised by clinical, functional or radiological decline at follow-up. Results: Progressive fibrosing phenotype was observed in 34 patients. There was a statistically significant difference in the incidence of the degree of skin symptoms between progressive patients and non-progressive patients. The presence of digital ulcers, modified Rodnan skin score ≥14 and mechanic’s hands was each associated with progression independently. Neurological symptoms were also more prevalent in the progressive group and peripheral neuropathy was an independent predictor. Additional independent predictors were UIP pattern on HRCT and baseline FVC <70% predicted. Conclusions: There was a significant association between progressive fibrosing CTD-ILD and cutaneous and neurological manifestations. Routine evaluation of skin and neurologic findings might be used to help identify high-risk patients who may benefit from more frequent monitoring and timely treatment optimization. Keywords: CTD-ILD, Progressive Fibrosing Phenotype, Cutaneous Manifestations, Neurological Manifestations, Interstitial Lung Disease.